Accumulation of differentiating intestinal stem cell progenies drives tumorigenesis - Zhai, Zongzhao; Kondo, Shu; Ha, Nati; Boquete, Jean-Philippe; Brunner, Michael; Ueda, Ryu; Lemaitre, Bruno (Nature Communications, 2015)
Stem cell self-renewal and differentiation are coordinated to maintain tissue homeostasis and prevent cancer. Mutations causing stem cell proliferation are traditionally the focus of cancer studies. However, the contribution of the differentiating stem cell progenies in tumorigenesis is poorly characterized. Here we report that loss of the SOX transcription factor, Sox21a, blocks the differentiation programme of enteroblast (EB), the intestinal stem cell progeny in the adult Drosophila midgut. This results in EB accumulation and formation of tumours. Sox21a tumour initiation and growth involve stem cell proliferation induced by the unpaired 2 mitogen released from accumulating EBs generating a feed-forward loop. EBs found in the tumours are heterogeneous and grow towards the intestinal lumen. Sox21a tumours modulate their environment by secreting matrix metalloproteinase and reactive oxygen species. Enterocytes surrounding the tumours are eliminated through delamination allowing tumour progression, a process requiring JNK activation. Our data highlight the tumorigenic properties of transit differentiating cells.